PERANCANGAN SISTEM INFORMASI BERBASIS WEB FRONT END (STUDI KASUS WARUNG NASI GORENG ABAH KARIM PALMERAH BARAT) - Malik Miftakhul Khaq; Tri Hidayati (CV. Multi Kreasi Media, 2023)
Fried rice stalls are a business that is in great demand by the middle and lower class, because in general many people understand and are familiar with fried rice sellers, Warung Nasi Goreng